INVESTIGATING REPRESENTATIONAL FLUENCY IN MODELING PROCESS: THE EXPERIENCE OF PRE-SERVICE TEACHERS WITH A CASSETTE PROBLEM - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2009)
As a part of larger research on pre-service teachers mathematical modeling abilities, this study investigates pre-service teachers' representational fluency, and its effect on modeling process in one modeling activity, that of cassette problem. The data is collected by students' individual and group written responses to the mathematical modeling activity, video-taped group discussions and classroom observation by the researcher. This study is conducted during the spring semester in 2007 and thirty three pre-service teachers were the participants of the study. The data showed that pre-service teachers have difficulty in transition between different modes of mathematical representations and this difficulty has an influence on modeling process.